Compositional bimodality of the nuclear genome of tobacco. - Matassi, G (1991)
We have studied the compositional distribution of six genes (or small multigene families) and of one family of transposable elements, Tnt1, in DNA fractions from tobacco (Nicotiana tabacum) separated according to base composition. We have shown that gene distribution is bimodal and that such bimodality is due to the different base composition of the two parental genomes of tobacco (N.sylvestris and N.tomentosiformis) and to the different parental origin of the genes tested. These results indicate a physical separation and an absence of extensive recombination of the parental genomes, which have been together in the tobacco nucleus for a small span of their evolutionary life, and a conservation of their compositional patterns, including gene localization.